2019
DOI: 10.4308/hjb.26.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Alpinumisoflavone from Erythrina poeppigiana (Leguminosae) Against Colon Cancer (WiDr), Cervical Cancer (Hela), and Hepatoma Cancer (HepG2) Cells

Abstract: Cancer is the second cause of death after cardiovascular diseases in the world. Anticancer prevention used can cause undesirable things. Flavonoids are secondary metabolites derived from natural products that are useful for anticancer treatment. This study was performed to observe the cytotoxic activity of alpinumisoflavone from Erythrina poeppigiana, toward cervical cancer (Hela), colon cancer (WiDr), and hepatoma cancer (HepG2) cells. The cytotoxic activity of alpinumisoflavone was tested using (3-[4,5-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
1
Order By: Relevance
“…However, the cytotoxicity against HeLa cancer cells obtained in our study was better than Dewangga, 2015 , Zuraida and Mariya, 2019 . Furthermore, the research from Herlina et al, 2019 , Mardiyaningsih and Ismiyati, 2014 produced a better IC 50 value compared to our study.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…However, the cytotoxicity against HeLa cancer cells obtained in our study was better than Dewangga, 2015 , Zuraida and Mariya, 2019 . Furthermore, the research from Herlina et al, 2019 , Mardiyaningsih and Ismiyati, 2014 produced a better IC 50 value compared to our study.…”
Section: Discussioncontrasting
confidence: 45%
“…Acetogenins from Annonaceae are cytotoxic against several cancer and tumor cells, such as pancreatic cancer cells (PACA-2), lung cancer cells (A549), colon, lung, and pancreatic tumors ( Nugraha et al, 2019 ). Research on Erythrina poeppigiana leaves showed an inhibitory concentration 50 (IC 50 ) value or inhibition against cervical cancer cells (HeLa) of 7.18 μg mL −1 ( Herlina et al, 2019 ). Bioactive compounds may be produced by endophytic microbes.…”
Section: Introductionmentioning
confidence: 99%
“…MCF7 cell lines were further treated with 1% penicillin-streptomycin (Sigma) in a humidified atmosphere with 5% CO 2 at 37°C entire the assay. Cell viability was analysed by an MTT colorimetric assay (3-[4, 5-dimethylthiazol-2-2,5 diphenyl tetrazolium bromide assay) (Roche) following the method as described elsewhere with some modifications (Herlina et al 2019). In short, the cells were seeded in 96-well plates at 1 × 10 4 and incubated at 37°C for Subsequently, the medium was removed, and the cells were treated with fresh medium containing 100 µg/ ml of sample diluted on DMSO and incubated for 48 h at 5% CO 2 ; 37°C.…”
Section: Cytotoxic Propertiesmentioning
confidence: 99%
“…MTT assay ; MTS assay [48][49][50]; WST assay [26]; SRB assay [51]; apoptosis with double staining method [34,45,47,52]; cell cycle analysis [53] gene expression analysis [36,37]; mitochondrial membrane potential Ψm (MMP), cytochrome c release analysis and NFkB translocation [49]; caspase activity and inhibitor assays [49]; protein extraction, protein array and western blotting analyses [49]; computational molecular docking and statistical analyses [45,50] HT-29 [24,49,50,54]; HCT-15 [26,27,43]; Colo205 [48]; WiDr [28,[30][31][32]34,[36][37][38][39][40][41][42]44,45,53]; HCT-116 [29,33,35,46,47,51]; CaCo-2 [49] Catechin 7-O-apiofuranoside and didesmethyl tocotrienol…”
Section: In Vitromentioning
confidence: 99%